The Influence of Greenwashing and Consumer Trust on Green Skincare Repurchase Intention through Green Brand Image among Gen Z in West Sumatra - Supryanita, Rina; Yasri; Rasyid, Rosyeni (Ilomata International Journal of Management, 2026)
This study aims to analyze the influence of greenwashing, consumer trust, and green brand image on the repurchase intention of green skincare products among Generation Z in West Sumatra Province. This study uses a quantitative approach with purposive sampling technique, which is the determination of samples based on certain criteria relevant to the research objectives, including respondents aged 18–26 years (Generation Z), active use of green skincare products for at least three months, and residing in the West Sumatra region. Data were obtained from 260 respondents and analyzed using Structural Equation Modeling (SEM). The findings indicate that greenwashing has a negative and significant effect on repurchase intention, suggesting that misleading or exaggerated sustainability claims reduce consumer interest in repurchasing. Conversely, consumer trust and green brand image positively and significantly affect repurchase intention, implying that confidence in sustainability claims and positive perceptions of green brand image foster repeat purchase behavior. However, the study reveals that green brand image does not mediate the relationship between greenwashing and repurchase intention but strengthens the influence of consumer trust. The study concludes that building consumer trust and reinforcing a credible green brand image are essential strategies for companies seeking to enhance consumer loyalty and long-term engagement in the growing sustainable skincare market.